Students’ Perceptions Regarding the Educational and Organizational Quality of a Nursing Program at a Chilean Private University - Vera-Millalén, Fernando (2018)
This paper aims to describe the students’ perception of the educational and organizational quality of the Nursing undergraduate program, at a Chilean private university. With a cross-sectional, mixed-method data design, it was decided that a self-administered 58-item questionnaire granted by the Chilean National Commission for Accreditation (CNA-Chile) should be used, with a response rate of 44.6% (n =104), of which 83 were women and 21 men (79.8% and 20.2%, respectively). Complementarily, focal group interviews were conducted. Estimations were performed with an exploratory, statistical and content analysis. Thus, results showed that students’ satisfaction with the nursing program is acceptable, but not entirely satisfactory (x̄=2.68). This implies a gap to overcome, provided that the CNA-Chile quality criteria are to be met. Consequently, a full range of curricular and organizational adjustments should be made in the unit being analyzed., a full range of curricular and organizational adjustments should be made in the unit being analyzed.